DATA QUALITY FOR HYDROGRAPHIC MEASUREMENTS: DATA QUALITY FOR HYDROGRAPHIC MEASUREMENTS - Stoykov, Evgeni (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The main objective of most hydrographic measurements is to obtain basic data for the compilation of navigation maps with a focus on characteristics that may affect safe navigation. The hydrographic map is the final product of hydrographic exploration. Its accuracy and compliance depend on the quality of the data collected during the measurements.